Hyperbaric oxygen therapy in the treatment of osteomyelitis - Albuquerque, Sandra Maria de Lima; Silva, Débora Alexandra Torres da; Santos, Tâmyssa Simões dos (JRG Journal of Academic Studies, 2023)
Introduction: Hyperbaric medicine is an area of innovation and continuous development, with discrepant clinical instructions. The purpose is, presumably, that the execution performed, may become a daily authenticity in the areas where it would be effective, so as to increase the number of patients successfully treated by this procedure, with a simultaneous decrease in spending on irrelevant treatments. Hyperbaric oxygen therapy is indicated for cases of acute vasculitis, refractory lesions, diabetic foot and osteomyelitis. Objective: is to highlight the effectiveness of hyperbaric oxygenation through a literary review, so that it can help spread knowledge about this therapeutic method, offer extensive and easy-to-understand visibility and thus stimulate interest in health professionals on the subject. Given the study performed, it can be concluded that Hyperbaric Oxygen Therapy is an efficient resource and can contribute to improving the quality of life of patients with diseases who benefit from its use, as long as it is indicated and applied correctly.Methodology: This integrative literature review study has a quantitative and descriptive character. The searches were carried out in the Scielo and Google Scholar databases. Results and discussions: Hyperbaric Oxygen Therapy corresponds in a preserved category resulting in reduced contraindications. The side effects of the hyperbaric oxygen therapy are respective to the variation of the pressure and/or toxicity of the oxygen. Conclusion: Hyperbaric oxygen therapy is an effective treatment for patients with chronic wounds, helping and accelerating the healing process of healing.